Efeitos maternos-fetais do tratamento com extrato aquoso da fruta de Buchenavia tomentosa durante a prenhez de ratas - Santos, Tainara de Paula Peixoto (2023)
The consumption of medicinal plants is widely used by the population as a treatment for various diseases. However, many plants used for herbal purposes can have toxic effects, especially if consumed during pregnancy. A plant used in folk medicine without scientific proof of its efficacy or toxicity during pregnancy is Buchenavia tomentosa, popularly known as mirindiba. Thus, the aim of this study was to evaluate the maternal and fetal effects of the aqueous extract of B. tomentosa fruit administered during pregnancy in female rats. To determine the compounds, present in the fruit, phytochemical analyzes of the fruit of B. tomentosa were carried out. To achieve the experiment, Wistar rats were mated and randomly distributed into four experimental groups (n=12 rats/group): rats treated with water (Control) or treated with B. tomentosa extract at a dose of 125 mg/kg (Treated Group 125), 250 mg/kg (Treated Group 250) and 500 mg/kg (Treated Group 500). The treatment with the aqueous extract of the fruit was carried out throughout the pregnancy (days 0 to 21), intragastrically (gavage). Body weight, food intake and water intake were weekly measured. On day 21 of pregnancy, laparotomy was performed with blood collection for biochemical analysis. The uterus was removed for verification of maternal reproductive performance data, and maternal organs, fetuses and placentas were weighed. Phytochemical analysis revealed the presence of phenolic compounds, including flavonoids and condensed tannins, as well as the presence of carotenoids and chlorophyll, resulting in the high antioxidant capacity of the extract. Treatment with B. tomentosa did not change body weight, water intake, maternal biochemical parameters, and postimplantation losses in any of the analyzed doses. Furthermore, the treatment did not alter fetal and placental weight. However, the treatment caused a decrease in food intake and relative weight of the kidneys and fetal anomalies at the highest dose used. The Treated 250 and 500 groups had a higher percentage of pre-implantation losses than the other groups. Thus, we can conclude that the plant has a toxic effect, especially at the highest dose.